In Silico Insights Into Bioactive Compounds of Wild Sumatran Turmeric (Curcuma sumatrana, Zingiberaceae) as Potent Antioxidant Candidates - Petrovsky, Ivan; Santoso, Putra; Fadil, Muhammad Syukri (Department of Biology, Faculty of Science and Technology, Syarif Hidayatullah State Islami, 2026)
Oxidative stress, characterized by an imbalance between reactive oxygen species and antioxidant defenses, contributes to various diseases. Natural products, particularly plant-derived compounds, offer promising therapeutic avenues due to their antioxidant potential. This study investigates the antioxidant properties of wild Sumatran turmeric (Curcuma sumatrana), an endemic Zingiberaceae species from Sumatra, through in silico computational analyses of its rhizome’s bioactive compounds. Twenty-two compounds were evaluated for drug-likeness using Lipinski’s Rule of Five, revealing 21 compounds (95%) as orally bioavailable. Predictive bioactivity via PASS Online identified six compounds with moderate antioxidant activity (Pa >0.3). Molecular docking against antioxidant enzymes (GPx, SOD, CAT) and the Keap1-Nrf2 complex demonstrated significant binding affinities. Notably, 9,10-Epoxy-12-octadecenoate exhibited superior binding to SOD (-5.75 kcal/mol), GPx (-6.42 kcal/mol), and Keap1-Nrf2 (-8.39 kcal/mol), outperforming native ligands. Abietic acid and N-Octylgallate also showed strong interactions with Keap1-Nrf2, suggesting activation of antioxidant response pathways. The results highlight C. sumatrana’s potential to modulate enzymatic antioxidants and Nrf2 signalling. The findings underscore the species’ role as a source of bioactive compounds with drug-like properties, advocating further exploration of its phytochemicals for mitigating oxidative stress-related pathologies while highlighting C. sumatrana as a viable candidate for developing natural therapeutics targeting redox imbalance.